1979
DOI: 10.1530/acta.0.0910351
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Diphosphonate-Blocked Bone Mineralization. Evidence That Calcitonin Promotes Mineralization

Abstract: There is much experimental evidence which indicates that calcitonin inhibits bone mineral resorption, but there are few data available in support of the proposal that calcitonin may also promote mineralization. Ethane-1-hydroxy-1,1-diphosphonate (EHDP) administered to immature rats inhibited mineralization as evidenced by widened tibial epiphyseal plates and decreased bone ash to dry weight ratios. Concurrent dosing with salmon calcitonin (SCT) prevented or reversed the EHDP-blocked mineralization in a dose de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…9] and rats [10]. On the other hand, it has no activity in promoting bone mineralization in EHDP-treated rats, although one of its metabolites, lc~,24.25-trihydroxyvitamin D:~, is active [12]. On the other hand, it has no activity in promoting bone mineralization in EHDP-treated rats, although one of its metabolites, lc~,24.25-trihydroxyvitamin D:~, is active [12].…”
mentioning
confidence: 99%
“…9] and rats [10]. On the other hand, it has no activity in promoting bone mineralization in EHDP-treated rats, although one of its metabolites, lc~,24.25-trihydroxyvitamin D:~, is active [12]. On the other hand, it has no activity in promoting bone mineralization in EHDP-treated rats, although one of its metabolites, lc~,24.25-trihydroxyvitamin D:~, is active [12].…”
mentioning
confidence: 99%
“…In contrast, calcitonin produces hypercalciuria in humans (15)(16)(17)(18) and sheep (19), possibly by its action on renal tubular reabsorption. The fact that the plasma calcium was lowered despite a decrease in calcium excretion suggests that ECT inter feres with bone resorption of calcium and may promote calcium bone deposition (20). In intact puppies, plasma phosphorus decreased and urinary phosphorus excretion tended to increase by ECT, whereas in all TPTX dogs, phosphorus excretion was unaffected or decreased.…”
Section: Effect Of Ect On Renal Hemodynamicsmentioning
confidence: 98%
“…Discussion EHDP possesses a structure and action similar to inorganic pyrophosphate which is considered to suppress calcification in vivo (Fleisch 1983 (Baxter et al 1974;Bonjour et al 1975). Boris et al (1979) pointed out that the EHDPtreated rat model could also prove useful when searching for compounds which stimulate mine¬ ralization. They also reported that concurrent administration of salmon calcitonin to EHDPtreated rats prevented or reversed the EHDPblocked mineralization, in a dose-dependent man¬ ner, and proposed that calcitonin may also pro¬ mote mineralization, in addition to its well known ability to inhibit bone mineral résorption.…”
Section: Histologicalfindingsmentioning
confidence: 99%
“…the same manner as seen in case of smooth muscle and myocardial cells, then our results indicate that intracellular concentrations of calcium might play an important role in the occurrence of accelerated calcification due to CT. In an animal model of human rickets, induced in rats by ethane-f-hydroxy-bl-diphosphonate (EHDP) administration, in large doses, it was found that administration of salmon calcitonin (Boris et al 1979) and [Asu17]eel calcitonin (CT) (Eguchi et al 1982ab) accelerated the calcifica¬ tion. The mechanisms involved in this accelera¬ tion are unknown.…”
mentioning
confidence: 99%